2019
DOI: 10.1017/jfm.2019.191
|View full text |Cite
|
Sign up to set email alerts
|

Relaminarising pipe flow by wall movement

Abstract: Received xx; revised xx; accepted xx)Following the recent observation that turbulent pipe flow can be relaminarised by a relatively simple modification of the mean velocity profile, we here carry out a quantitative experimental investigation of this phenomenon. Our study confirms that a flat velocity profile leads to a collapse of turbulence and in order to achieve the blunted profile shape, we employ a moving pipe segment that is briefly and rapidly shifted in the streamwise direction. The relaminarisation th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 36 publications
1
9
0
Order By: Relevance
“…Although those absolute values should be treated with caution and might vary for different FMDs (with differently sized honeycombs etc.) and different pipe diameters, the trend that the M-shape is advantageous compared to a mere flattening of the profile is consistent with observations of [2] and [3].…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…Although those absolute values should be treated with caution and might vary for different FMDs (with differently sized honeycombs etc.) and different pipe diameters, the trend that the M-shape is advantageous compared to a mere flattening of the profile is consistent with observations of [2] and [3].…”
Section: Resultssupporting
confidence: 89%
“…The velocity profiles of all successfully controlled, i.e. relaminarizing flows considered by [1], [2] and [3] are shown to have a substantially reduced transient growth. We applied the same procedure here to the exemplary velocity profiles shown in fig.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Recently, there has been a series of experiments (Kühnen et al 2018 a , b ; Kühnen, Scarselli & Hof 2019; Scarselli, Kühnen & Hof 2019) showing that the flattening of a turbulent streamwise velocity profile in a pipe flow leads to a full collapse of turbulence for Reynolds numbers up to , thus reducing the frictional losses by as much as 90 %. Different experimental techniques were employed to obtain the flattened base profile – e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Very recently, Kühnen et al (2018) and Scarselli et al (2019) numerically and experimentally demonstrated that controls aiming at decelerating the flow in the center of a channel and accelerating it in the near-wall region lead to relaminarization of turbulent flow. In other words, making the turbulent mean velocity profile 'flattened' successfully suppresses the turbulence intensities.…”
Section: Introductionmentioning
confidence: 99%